2009
DOI: 10.1089/sur.2008.0004
|View full text |Cite
|
Sign up to set email alerts
|

Acute Uncomplicated Appendicitis: Case Time of Day Influences Hospital Length of Stay

Abstract: Operative time of day was a surprisingly important determinant of hospital LOS. Efforts to minimize LOS and optimize resource utilization should balance operating room availability, surgeon preferences, shift-dependent costs, nursing policies, and hospital systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A 2005 study demonstrated that patients who had operations earlier in the day had longer post-operative length of stay. 10 Bhangu et al ., in a setting much different from SCOAP hospitals, showed that NA, use of laparoscopy, and consultant ( i.e. , attending) presence in the OR varied substantially by time-of-day in a group of 95 hospitals, mostly in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…A 2005 study demonstrated that patients who had operations earlier in the day had longer post-operative length of stay. 10 Bhangu et al ., in a setting much different from SCOAP hospitals, showed that NA, use of laparoscopy, and consultant ( i.e. , attending) presence in the OR varied substantially by time-of-day in a group of 95 hospitals, mostly in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Within these time frames, the probability of a successful laparoscopic procedure is higher and both LOS and hospital costs are lower. [16–18] Delays beyond 18 h do not appear to increase the incidence of surgical site infections or other complications, but are costly and increase the patient's LOS. It is unclear why there was delay in surgery for patients in this group (Group 4) of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mean LOS for AA and AC from 2011 to 2017 were one and three days, respectively; one day less than the two additional Winnipeg hospitals performing these procedures. Multiple factors have been shown to impact LOS for AA patients, including time of presentation, perforation, and time of surgery [21-22].…”
Section: Discussionmentioning
confidence: 99%